Pengembangan Kurikulum Berorientasi Merdeka Belajar-Kampus Merdeka Program Studi S1 Tadris Bahasa Indonesia Fakultas Tarbiyah IAIN Kediri - Iwan Marwan; M Badrus Solichin (Institut Agama Islam Negeri Curup, 2022)
This research is oriented to the study of curriculum development in the Indonesian Language Education Study Program, Faculty of Tarbiyah IAIN Kediri, which is a follow-up to the policy of the Minister of Education and Culture by adapting the curriculum from KKNI to MBKM. The method used to answer this is a literature study, by making several guidelines, guidelines and journal articles that are relevant to the research topic. The stages of the research include (1) collecting relevant data through a literature study, (2) reviewing the literature obtained by concluding the main topic regarding the implementation of the independent learning-campus curriculum. The results of this study found that the MBKM curriculum development carried out included planning activities, learning processes, process assessment standards, and MBKM Learning Monitoring and Evaluation. Then from the results of curriculum development, it will be used as a curriculum development document at the Indonesian Language Education Study Program, IAIN Kediri, in implementing the MBKM curriculum in the 2022/2023 academic year